ESTIMASI SUMBER DAYA NIKEL LATERIT MENGGUNAKAN METODE INVERSE DISTANCE WEIGHT (IDW) PADA PT X, MALUKU UTARA - Juan D E Nanlohy; Irfan Marwanza; Taat Tri Purwiyono (PT. Hasba Edukasi Mandiri, 2026)
Mineral resource estimation is a fundamental stage in mine planning that determines the economic viability of a deposit. This study aims to estimate laterite nickel resources using the Inverse Distance Weighting (IDW) method at a deposit in PT X, North Maluku, through an integrated approach encompassing variogram analysis, strict geological domain separation, and quantitative validation. The data consist of secondary exploration drilling data from 42 drill holes, including collar, survey, assay (Ni, Fe, SiO2), and lithology. Data processing was carried out using Leapfrog for wireframe geological modeling, Snowden Supervisor for statistical and variography analysis, and Isatis.neo for compositing, block modeling, and IDW estimation. Limonite and saprolite domains were separated using hard boundary. Estimation results show a total nickel resource of 9,878.87 tonnes, comprising 3,469.31 tonnes in the limonite zone (Ni grade 1.11%) and 6,409.56 tonnes in the saprolite zone (Ni grade 1.90%). Cross-validation yielded IDW correlation coefficients ranging from 0.69 to 0.76, with Ni Root Mean Square Error (RMSE) of 0.24 for limonite and 0.50 for saprolite. The resulting IDW block model realistically represents grade distribution in accordance with laterite genesis principles and can serve as a reference for subsequent mine planning.